GADGET-2 simulation for active galactic nuclei feedback in galaxy NGC 5252 - M. Boonmalai (2020)
© Published under licence by IOP Publishing Ltd. We present a numerical simulation of active galactic nuclei (AGN) feedback in galaxy NGC 5252, while galaxy has gas, halo, disk, and bulge particles. We set up one bulge particle's mass to represent the black hole mass. According to the result from numerical simulation of active galactic nuclei feedback, we interpret that the gas provides some gas feedback at large distant approximately around 10 kpc. We generate initial condition, as known as IC fle of the galaxy, including a stellar disk and gas particles following an exponential density profle. A dark matter halo and a stellar bulge follow a Dehnen density profle. GADGET-2 was used to calculate the distribution of particles in galaxy simulation, which is based on smoothed particle hydrodynamics method. Ultimately, we study the gas feedback of active galactic nuclei in the form of outfow gas with numerical simulations. From preliminary result show that the gas particles seem to evolve with time and concentrate on the later time near 5 to 10 kpc.